Dance of the bones : a J. P. Beaumont and Brandon Walker novel - Jance, Judith A. (Jance, Judith A. J. P. Beaumont mysteries, 2015)
"Years ago, Amos Warren, a prospector, was gunned down out in the desert and Sheriff Brandon Walker made the arrest in the case. Now, the retired Walker is called in when the alleged killer, John Lassiter, refuses to accept a plea deal that would release him from prison with time served. Lassiter wants Brandon and The Last Chance to find Amos's "real" killer and clear his name. Sixteen hundred miles to the north in Seattle, Mel Shames is leaving the Special Homicide Investigation Team thanks to her new job as the Police Chief in Bellingham. Her husband, crack investigator J. P. Beaumont, is dealing with the realities of life as the "chief's spouse"--and the fact that S.H.I.T. has been unexpectedly and completely disbanded. Brandon Walker's search to find the truth about Warren's killer will lead him from the sunny, hot desert of Cochise County to the damp, cool forests of the Pacific Northwest, where he eventually meets Beau, thanks to lawyer Ralph Ames who connects them. Their meeting proves all too crucial, for soon they must pool their personal and professional expertise to save Mel when her life is threatened by a gun-toting madman who is all too close to her" --